An Application of the Hercudet Non-Electric Delay Initiation System to Underground Pillar Blasting - W Russell (International Society of Explosives Engineers, 1985)
The Hercudet Non-Electric Delay Blasting Cap System provides a means of achieving greater flexibility in the use of delays, using totally enclosed gas detonation circuits which eliminate the concussive effects of detonating cord trunklines in the confinement of access tunnels beneath pillars of ore. This is an account of one such pillar blast.